Randomized controlled trial of TDCS on cognition in 201 seniors with mild neurocognitive disorder - Hanna Lu; Sandra Sau Man Chan; Wai Chi Chan; Cuichan Lin; Calvin Pak Wing Cheng; Lam Linda Chiu Wa (Annals of Clinical and Translational Neurology, 2019)
Abstract Objective To examine the efficacy and safety of combined transcranial direct current stimulation (tDCS) and working memory training (WMT) in enhancing the cognitive functions for individuals with mild neurocognitive disorder due to AD (NCD‐AD). Methods In this double‐blind, sham‐controlled randomized clinical trial (RCT), 201 patients with NCD‐AD were randomly assigned for a 4‐week intervention of either a combination of tDCS and WMT, sham tDCS and WMT, or tDCS and control cognitive training (CCT). Global cognition and domain‐specific cognitive function were assessed before and after the intervention with Alzheimer's disease assessment scale‐cognitive subscale (ADAS‐Cog), category verbal fluency test, logical memory, digit, and visual span tests. Results Study participants did not show intervention group differences in baseline demographics, or cognitive characteristics (ANOVA). Cognitive enhancement was found across three groups after 4 weeks intervention. Combined tDCS‐WMT group showed significantly greater improvement compared with single‐modality groups in delayed recall (P = 0.043, η2 = 0.036) and working memory capacity (P = 0.04, η2 = 0.038) at 4th week, and logical memory at 12th week (P = 0.042, η2 = 0.037). Adverse events, including skin lesions (2.2%), were similar between groups. Interpretation tDCS or WMT could be a safe, feasible, and effective intervention for individuals with NCD‐AD. A combination of tDCS and WMT presents greater cognitive enhancement, which may highlight the potential synergistic effects of combined modality intervention on cognition.